Analysis and passivity-based control of a zero-voltage-transition PWM boost converter - Li, De Hua. (2008)
Derive the average model of the ZVT-PWM boost converter using the generalized state-space averaging technique. Verify the accuracy of the derived average model by comparing it with the average model. Develop nonlinear controllers for the regulation of the boost converter using the passivity-based approach.